(3HGH aj cjajI GdYed HGdcQg ef cJGH LGeY GdeHGOF hGdZGjGJs - (3CHh Ydj TQa GdOjf GdMSf Hf Ydj Hf YeQ GdeQGcTj,J (B660 (3g` s
(3ChdgG (B:s
(3HgPg GdBdg bO hbY ddCbOejf HgG aVd GYJHGQgG ai JCedgG ef GdefGaY s
(3BNQgG (B:s
(3aEf Jdc GdCehQ jecf QOgG Edi Cbd efgG hGfG QGYjJ MGd GdJYdje s
(3agh jTJed Ydi U aUdkGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B203 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B286s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B1 - (3U (B25 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B572s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjg (B((3ejbGJ (B124) s
Keywords: (3Gdadcs